The Human Factor of Cybercrime. (August 2022) - Dupont, Benoît; Holt, Thomas
This volume highlights the central role of the human factor in cybercrime and the need to develop a more interdisciplinary research agenda to understand better the constant evolution of online harms and craft more effective responses. The term "human factor" is understood very broadly and encompasses individual, institutional, and societal dimensions. It covers individual human behaviors and the social structures that enable collective action by groups and communities of various sizes, as well as the different types of institutional assemblages that shape societal responses. This volume is organized around three general themes whose complementary perspectives allow us to map the complex interplay between offenders, machines, and victims, moving beyond static typologies to offer a more dynamic analysis of the cybercrime ecology and its underlying behaviors. The contributions use quantitative and qualitative methodologies and bring together researchers from the United States, the United Kingdom, the Netherlands, Denmark, Australia, and Canada.